New effective thermal conductivity model for the analysis of unconstrained melting in an entire thermal storage tank. (August 2020) - Kumar, Binit; Abhishek, Awasthi; Chung, Jae Dong
Highlights: A new effective thermal conductivity model is proposed. An entire tank composed of 9 × 9 × 20 capsules was modeled using the proposed model. Density differences between solid and liquid PCM was incorporated in the model. System performance was estimated with acceptable accuracy and computation time. Abstract: A new effective thermal conductivity model is proposed for full tank simulation, including the effect of the different densities of the solid PCM and liquid PCM. Firstly, the proposed model was validated for one capsule and then for one column with four layers of capsules. Further, it was extended to a thermal storage tank composed of 9 × 9 × 20 capsules in a simple cubic arrangement. Dissimilar melting behavior was observed depending on the different positions of the capsules in the tank, which illustrated the importance of simulating the entire tank. Also, because of the density difference between the liquid and solid PCM, the movement of solid PCM results in contact melting, which enhances melting speed compared with that of constrained melting. The validation result for the proposed unconstrained effective thermal conductivity model for single capsule showed root mean square error (RMSE) of 0.008 with respect to the refined numerical model. The constrained melting model highly under-estimated the melting speed compared to the unconstrained melting model (RMSE of 0.17). The two main obstacles to accurately estimating the performance of thermal storage systems were overcome by the proposed model.